A test generation strategy for pairwise testing. - Kuo-Chung Tai (IEEE Transactions on software engineering)
Pairwise testing is a specification-based testing criterion which requires that for each pair of input parameters of a system, every combination of valid values of these two parameters be covered by at least one test case. The authors propose a novel test generation strategy for pairwise testing